[Comment] Long term oncologic outcomes of natural orifice specimen extrac tion surgery versus conventional laparoscopic-assisted resec tion in the treatment of rectal cancer: a propensity-score matching study - Wang Tao (结直肠肛门外科, 2022)
[Background] Natural orifice specimen extraction surgery (NOSES) has been increasingly applied in radical surgery of abdominal and pelvic organs, but it is still in the exploratory stage. There is insufficient evidence to prove its efficacy. [Methods] From January 2013 to June 2017, a total of 351 patients diagnosed with rectal cancer were eventually included in this study. Patients who underwent NOSES were assigned to the NOSES group, while patients undergoing conventional laparoscopic assisted resection were assigned as to the LAP group. Propensity score matching was used to align clinicopathological features between the two groups. [Results] From the perioperative data and postoperative follow-up results of both groups, patients in the NOSES group had less intraoperative bleeding (47.0 ± 60.4 ml vs 87.1 ± 101.2 ml, P = 0.011), shorter postoperative gastrointestinal recovery (50.7 ± 27.3 h vs 58.6 ± 28.5 h, P = 0.040), less postoperative analgesic use (36.8% vs 52.8%, P = 0.019), lower postoperative pain scores (P < 0.001), lower rate of postoperative complications (5.7% vs 15.5%, P = 0.020), more satisfaction with body image (P = 0.001) and cosmesis (P < 0.001) postoperatively. The NOSES group had a higher quality of life. Moreover, there was no significant difference in overall survival (OS) and disease-free survival (DFS) between the two groups. [Conclusion] NOSES could be a safe and reliable technique for radical resection of rectal cancer, with better short-term outcomes than conventional laparoscopy, while long-term survival is not significantly different from that of conventional laparoscopic surgery.